1980
DOI: 10.1007/bf00290227
|View full text |Cite
|
Sign up to set email alerts
|

An extra idic(15p)(q11) chromosome in Prader-Willi syndrome

Abstract: Using a nonfluorescent AT-specific oligopeptide antibiotic, Distamycin A, on DAPI fluorescent banding of human chromosome (DA-DAPI) as described by Schweizer et al. (1978), we have detected an additional idic(15p) chromosome in a patient with typical Prader-Willi syndrome. On the basis of the evidence available in previous studies and of our own present results, we suspect that the fundamental genetic error in the syndrome is not caused by a chromosome aberration but by a gene aberration on chromosome 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The two abnormal gametes ( c ) will contain, respectively, 23 and 22 chromosomes. nance of isodicentrics originated from a single chromosome 15 (415) in PWS patients with extra inv dup(l5) chromosome [Fujita et al, 1980;Wisniewski et al, 1980;Ledbetter et al, 1982;Mattei et al, 1983, case 9;Zellweger et al, 19871 is in contrast with the predominance of inv dup(l5) resulting from interchanges between homologous chromosomes 15 as observed in a sample of variously ascertained inv dup(l5) chromosomes [Maraschio et al, 19881. 6) The rarity of extra derivatives resulting in 15q proximal tertiary trisomy [Smith et al, 19891 that could, in part, be related to the conversion of the hypothetical derivative into a n idic(l5) [Mattei et al, 19841. Analogously, the analysis of 11 translocations of chromosome 22 associated with DiGeorge anomaly [Greenberg et al, 19881 shows that apparently nonreciprocal unbalanced translocations (with a 45-chromosome constitution) are often de novo.…”
Section: Discussionmentioning
confidence: 93%
“…The two abnormal gametes ( c ) will contain, respectively, 23 and 22 chromosomes. nance of isodicentrics originated from a single chromosome 15 (415) in PWS patients with extra inv dup(l5) chromosome [Fujita et al, 1980;Wisniewski et al, 1980;Ledbetter et al, 1982;Mattei et al, 1983, case 9;Zellweger et al, 19871 is in contrast with the predominance of inv dup(l5) resulting from interchanges between homologous chromosomes 15 as observed in a sample of variously ascertained inv dup(l5) chromosomes [Maraschio et al, 19881. 6) The rarity of extra derivatives resulting in 15q proximal tertiary trisomy [Smith et al, 19891 that could, in part, be related to the conversion of the hypothetical derivative into a n idic(l5) [Mattei et al, 19841. Analogously, the analysis of 11 translocations of chromosome 22 associated with DiGeorge anomaly [Greenberg et al, 19881 shows that apparently nonreciprocal unbalanced translocations (with a 45-chromosome constitution) are often de novo.…”
Section: Discussionmentioning
confidence: 93%
“…There have been multiple reports of individuals with a small bisatellited derivative 15 chromosome which, in effect, means that these individuals have four copies of the centromere and short arm. Extra inv dup( 15) chromosomes have been reported in normal individuals (Steinback et al, 1983) as well as in patients with Prader-Willi syndrome (Fujita et al, 1980;Wisniewski et al, 1980). In view of the inconsistent information available at the time the amniocentesis result was obtained, we counselled the family that based on their own family history the risk of abnormality in the fetus seemed to be small.…”
Section: Discussionmentioning
confidence: 99%
“…However other chromosomal aberrations have also been reported, e.g. balanced rearrangements with two centromeric heterochromatic regions (Fraccaro et al 1977, Fleischnick et al 1979 or cases with an extra marker chromosome, in some instances identified as an idic (15) (Michaelson et al 1979, Fujita et al 1980, MoriC-PetroviC et al 1981, Ledbetter et al 1981. Fraccaro et al (1983) recently described seven cases, four of which showed deficiencies of chromosome 15 material, two apparently were balanced and one showed excess of unidentified chromosomal material.…”
Section: Discussionmentioning
confidence: 99%